Synthesis and Characterization of Hydrated Holmium and Erbium Carbonates - SONG, LIU; RONGJUN, MA (Asian Journal of Chemistry, 2010)
Crystalline hydrated holmium and erbium carbonates were synthesized using ammonium bicarbonate as precipitant. The holmium and erbium carbonates prepared are hydrated normal carbonates and the structure and properties were investigated by XRD, SEM, TG and IR techniques. The holmium and erbium carbonates consist of spherical aggregates of crystallites. The structures are closely related to those of tengerite type rare earth carbonates in the literature. The IR data for the holmium and erbium carbonates show the presence of two different carbonate groups (bidentate and unidentate carbonates) in the unit cell. In the process of thermal decomposition of the holmium and erbium carbonates to oxide, no stable intermediate was detected.